Comparison of ISO-GUM and Monte Carlo methods for the evaluation of measurement uncertainty: Application to direct cadmium measurement in water by GFAAS - Theodorou, D; Meligotsidou, L.; Karavoltsos, S.; Burnetas, A; Dassenakis, M.; M. Scoullos (Talanta, 2011)
The propagation stage of uncertainty evaluation, known as the propagation of distributions, is in most cases approached by the GUM (Guide to the Expression of Uncertainty in Measurement) uncertainty framework which is based on the law of propagation of uncertainty assigned to various input quantities and the characterization of the measurand (output quantity) by a Gaussian or a t-distribution. Recently, a Supplement to the ISO-GUM was prepared by the JCGM (Joint Committee for Guides in Metrology). This Guide gives guidance on propagating probability distributions assigned to various input quantities through a numerical simulation (Monte Carlo Method) and determining a probability distribution for the measurand. In the present work the two approaches were used to estimate the uncertainty of the direct determination of cadmium in water by graphite furnace atomic absorption spectrometry (GFAAS). The expanded uncertainty results (at 95% confidence levels) obtained with the GUM Uncertainty Framework and the Monte Carlo Method at the concentration level of 3.01 μg/L were ±0.20 μg/L and ±0.18 μg/L, respectively. Thus, the GUM Uncertainty Framework slightly overestimates the overall uncertainty by 10%. Even after taking into account additional sources of uncertainty that the GUM Uncertainty Framework considers as negligible, the Monte Carlo gives again the same uncertainty result (±0.18 μg/L). The main source of this difference is the approximation used by the GUM Uncertainty Framework in estimating the standard uncertainty of the calibration curve produced by least squares regression. Although the GUM Uncertainty Framework proves to be adequate in this particular case, generally the Monte Carlo Method has features that avoid the assumptions and the limitations of the GUM Uncertainty Framework. © 2010 Elsevier B.V. All rights reserved.
Keywords: Absorption spectroscopy; article; Atomic; Atomic absorption spectrometry; cadmium; Calibration curves; chemistry; comparative study; Concentration levels; Confidence levels; Direct determination; Estimation; Gaussians; GFAAS; Graphite furnace atomic absorption spectrometry; Guide to the expression of uncertainty in measurements; Guidelines as Topic; ISO-GUM; Least squares regression; Measurand; Measurement theory; Measurement uncertainty; Models; MONTE CARLO; Monte Carlo method; Monte Carlo methods; Numerical methods; Numerical simulation; practice guideline; Probability distributions; Propagation of distributions; Sources of uncertainty; spectrophotometry; standard; Standard uncertainty; T-distribution; Theoretical; theoretical model; uncertainty; Uncertainty analysis; Uncertainty estimation; Uncertainty evaluation; Water absorption